Pressurised putty technique: A technical report - Ong, Joshua Ee Xin (IIUM Journal of Orofacial and Health Sciences, 2023)
The surface detail reproducibility of conventional putty impressions is hindered by high viscosity and low flowability. In the plastic industry, injection moulding application utilizes an influx of pressure to achieve better flowability. Leveraging this concept, this technical report investigated the impact of pressure on surface detail reproducibility and structural homogeneity, featuring the pressurised putty technique. Surface detail reproducibility and structural homogeneity of three techniques (non-pressurised, putty & light body wash and pressurised) were visually assessed and differences in surface detail reproducibility were observed among all techniques. Whilst a pressurised clear-based putty index presented a more uniform glassy finish. The outlined technique suggests a simplistic and cost-effective way of improving a putty index, which may benefit many clinicians in terms of prosthodontic success.